Modern trends of international trade and prospect of development of the market ICT-goods - Davydzenka, Elena L.; Molchan, Yana V. (Journal of the Belarusian State University. Economics, 2018)
The article contains an analysis of the current trends in the development of international trade, including such a dynamic segment as ICT goods. It is noted that Eastern Asia and the Pacific remain the leader among the regions in terms of share of exports and imports of ICT goods. Leading exporters and importers of ICT goods at the country level and advanced technology companies are singled out. It is predicted that the future of the ICT market for the next 10 years is connected with the implementation of the accumulated technological potential of the Asian market, which will push the markets of European countries and the USA. The main arguments for this assumption are, firstly, the growing level of information and communication technologies in the region, especially in the Southeast Asian countries, as well as the powerful technology companies emerging in the Asian region, which demonstrate colossal successes on a global scale even at the initial stages of activity.